A COMPARATIVE ANALYSIS OF MRI PERFUSION PARAMETERS IN YOUNG PATIENTS WITH VARIOUS METABOLIC SYNDROME PHENOTYPES - Bobojonov, Shahboz; Gaibiev, Akmal (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
In recent years, there has been an increase in the incidence of metabolic syndrome among young people: according to epidemiological studies, the prevalence of metabolic syndrome in the 18-40 age group reaches 5-10% and continues to increase due to a sedentary lifestyle and unbalanced diet (1). Metabolic syndrome is accompanied by microcirculatory disorders and endothelial dysfunction, which in the preclinical stages manifest as changes in cerebral blood flow. Early diagnosis of such disorders is critical for preventing cognitive and vascular complications (2).